Effects of Economic Partnership Agreements Between Ecowas and the EU on Trade, Revenue and Welfare of Agricultural Trade of Ecowas Bloc - Collins Sunday Nwali; Oguntade Adegboyega Eyitayo; Mafimisebi Taiwo Ejiola; Obisesan Adekemi Adebisola (Turkish Journal of Agriculture: Food Science and Technology)
This study examined the Effects of Economic Partnership Agreements between ECOWAS and the EU on Trade, Revenue and Welfare of Agricultural trade of ECOWAS bloc. The specific objectives of the study were to:(i) estimate the potential trade creation and diversion effects of EPA on agricultural trade of ECOWAS bloc, (ii) estimate the potential revenue effects of EPA on agricultural trade of ECOWAS bloc and (iii) estimate the potential welfare effects of EPA on agricultural trade of ECOWAS bloc. World Integrated Trade Solutions provided access to an online secondary data as classified by United Nations Harmonized system. The result on the potential trade creation and diversion effects of EPA on both trading blocs showed that ECOWAS will gain US$198.9million in trade creation and lose US$58.4 million in Trade Diversion. On the other hand, there will be no trade creation for EU with negligible trade diversion of – US$0.2million. The result showed total potential tariff revenue losses of US$366.4million for ECOWAS bloc post EPA. On the other hand, EU will lose (US$951.8million) its agricultural products post EPA. The result further showed potential welfare gain of US$27.6million for consumers of ECOWAS bloc. On the other hand, there will be welfare gain of the EU at US$243.5million for their consumers post EPA. Among all the recommendations, the study therefore points out that the on-going EPA negotiations between ECOWAS and the EU need not to be hurriedly signed by ECOWAS bloc. Also, ECOWAS needs to strengthen its agricultural production efficiency to be able to compete globally and encourage its individual countries to return to a single digit borrowing interest rate to encourage more investment by local agricultural producers if they want to enjoy the benefits of trade treaties at long run if EPA is eventually signed.